On retaliation: towards an interdisciplinary understanding of a basic human condition - Turner, Bertram; Schlee, Günther (Integration and conflict studies, 2017)
On retaliation : conceptual plurality, transdisciplinary research, rifts, blurrings -- And translations / Bertram Turner -- Revenge and retaliation : a social-functionalist approach / Mario Gollwitzer and Arne Sjostrom -- In the heart of the moment : the influence of visceral factors on retaliation / Robert J. Bies and Thomas M. Tripp -- A criminal is a victim is a criminal? : an economist's view on the victim-offender overlap / Horst Entorf -- Laypeople's reactions to deviancy as determined by retributive motives / Margit E. Oswald -- Violent crimes and retaliation in the European criminal justice system between the seventeenth and nineteen centuries / Karl Harter -- Crime in motion : predation, retaliation and the spread of urban violence / Richard Wright, Volkan Topalli and Scott Jacques -- Crime and punishment : intentionality and diya in Algeria and Sudan / Yazid Ben Hounet -- 'Bewitched people and bad luck everywhere!' : disputing and magical retaliation in siSwati-speaking Southern Africa / Severin Lenart -- Forum shopping as retaliation in disguise : how nomadic Fulbe condemn retaliation and forum shopping, but practise them anyway / Albert K. Drent -- Customary law and the joys of statelessness : Somali realities beyond libertarian -- Fantasies / Gunther Schlee -- Retaliation in postwar times : an analysis of the rhetoric and practices of retaliation in Bamyan, Afghanistan, 2009 / Friederike Stahlmann -- The International Criminal Court reparation system : punishment, retaliation, restoration / Pietro Sullo -- Conclusion : retaliation in specific spheres of effectiveness / Bertram Turner